Stimulation of Managers in Regional Enterprises - Belkin, Vladimir Nikiforovich; Belkina, Nadezhda Andreevna; Antonova, Olga Anatolyevna (Economy of Regions, 2018)
Most of the principles related to top managers work incentives were inherited from the planned economy that produces demotivation and opportunistic behaviour. Remuneration is a commercial secret and shall not be disclosed. The system of top managers’ stimulation is unbalanced and does not motivate them to achieve medium- and long-term goals of the company. The study pays great attention to the development of managers’ stimulation policies, the transparency of remuneration, correlation between pay and performance. We provide practical examples of foreign and national experience, showing the ability to ensure the transparency of remuneration of managers, and the relation between compensation and performance. These examples show that managers’ remuneration amount does not always correspond to the efficiency of enterprises and return on capital. To solve these problems, we offer to develop philosophy and policy for the stimulation of managers in enterprises. It will allow to find a balance between the interests of shareholders and managers. Furthermore, this philosophy will have a positive impact on the competitiveness of enterprises in a region. The policy of stimulating managers should include certain key areas. Firstly, it should ensure the competitiveness of managers’ remuneration. Secondly, it implies studying the motives of managers’ work and the integration of these motives in the development of incentive system for the managers. Thirdly, it should include an optimal combination of elements to stimulate labour: base salary, material and social remuneration, short and long-term remuneration, etc. And last, it should consider the indicators and norms of enterprise’s effectiveness as well as the assessment of working results of managers. The results of this research can be used for further study of the stimulation of managers’ work in Russian companies. They can also be used in practice for the analysis of labour incentives of managers and their impact on the development of enterprises.